Prof. Juozas Eretas’ views on the history of Lithuanian culture: from „Tėvynės sargas" to „Naujoji Romuva" - Vasiliauskienė, Aldona (Lietuvos istorijos studijos, 1997)
Numerous scientists and public figures contributed their share of honest, devoted work to the foundation of the independent Lithuanian state. The activities of Juozas Eretas (1896-1984), a Swiss, occupied a distinguished place among outstanding Lithuanians of interwar Lithuania. At the age of 23, Juozas Eretas arrived in Lithuania. With youthful zeal and a Western European outlook, he plunged into activities which demanded a great deal of ingenuity and devotion. As soon as he completed his work in one area, he would immediately start work in a new one. This strenuous life came to an end in 1928, due to his failing health. In 1919-1940, Eretas took an active part in political and public life. He also did pedagogical work and research work. His public career, so vehement in the beginning, slowly, little by little, gave way to research work. Juozas Eretas made a considerable contribution to the updating and reorganization of the main spheres of his public activities, which principally dealt with sobriety, sport, and youth organizations. He was the founder of the Lithuanian News Agency (ELTA). His merits for efforts to achieve recognition of Lithuania de jure are also remarkable. He participated in organizing committees in Kaunas, the aim of which was to set up higher courses and the Lithuanian Catholic University, in 1931. He was one of the initiators who organized the congresses of the Lithuanian Catholic Academy of Sciences. He also edited their transactions. Prof. Juozas Eretas’ views on the history of Lithuanian culture over the period of 35 years (1896-1931) are of great importance, especially when his mature age of 75 is taken into consideration. Full understanding of the covered road „will make it possible to understand the present and at least partially to foresee its further direction," wrote Juozas Eretas in his study, „Two Generations in the Service of our Christian Culture," p. 51. It covered the period dating from 1896, the year when „Tėvynės Sargas" was founded, to 1931, when „Naujoji Romuva" was established. The article presents Juozas Eretas’ ideas and views stated in the above-mentioned study.